Petal, Sepal, or Tepal? B-Genes and Monocot Flowers. (January 2017) - Dodsworth, Steven
Abstract : In petaloid monocots expansion of B-gene expression into whorl 1 of the flower results in two whorls of petaloid organs (tepals), as opposed to sepals in whorl 1 of typical eudicot flowers. Recently, new gene-silencing technologies have provided the first functional data to support this, in the genus Tricyrtis (Liliaceae).